Предмет: Алгебра, автор: ichkannnichtzahlen

упростить выражение

Приложения:

Ответы

Автор ответа: сок111213
4

( {b}^{ \frac{5}{6}   }  ){}^{3}  \times  \sqrt[4]{ {b}^{3} }  = b {}^{ \frac{5 \times 3}{6} }  \times { b}^ \frac{3}{4} = b {}^{ \frac{5}{2} }  \times  b {}^{ \frac{3}{4} }  =  {b}^{ \frac{5}{2}  +  \frac{3}{4} }  =  {b}^{ \frac{10 + 3}{4} }  =  {b}^{ \frac{13}{  4} }  =  \sqrt[4]{ {b}^{13} }  =  \sqrt[4]{ {b}^{12}  \times b}  = b {}^{3}  \sqrt[4]{b}

Автор ответа: dimaogol2000
0

Ответ:

Объяснение:

(b^{\frac{5}{6} })^3*\sqrt[4]{b^3} =b^{\frac{5}{2} }*b^{\frac{3}{4} }=\sqrt[4]{b^{13}}

Похожие вопросы